2018
DOI: 10.3390/s18061784
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of GPS Precise Point Positioning Under Different Geomagnetic Storm Conditions during Solar Cycle 24

Abstract: The geomagnetic storm, which is an abnormal space weather phenomenon, can sometimes severely affect GPS signal propagation, thereby impacting the performance of GPS precise point positioning (PPP). However, the investigation of GPS PPP accuracy over the global scale under different geomagnetic storm conditions is very limited. This paper for the first time presents the performance of GPS dual-frequency (DF) and single-frequency (SF) PPP under moderate, intense, and super storms conditions during solar cycle 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
2
30
2
Order By: Relevance
“…At the same time, they also used different instruments or data, including ground‐based GNSS data, ionosondes data, TSX data, GRACE data, Swarm data, GUVI, Jason‐2, and GPS data on Jason‐2 for understanding the geomagnetic storm (Astafyeva et al, 2015; Chen et al, 2016; Jin et al, 2017; Kuai et al, 2016; Nava et al, 2016; Prikryl et al, 2016). Meanwhile, the GPS scintillation events, LOL, and its effects on positioning service during the main phase were also demonstrated (Jacobsen & Andalsvik, 2016; Jin & Oksavik, 2018; Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, they also used different instruments or data, including ground‐based GNSS data, ionosondes data, TSX data, GRACE data, Swarm data, GUVI, Jason‐2, and GPS data on Jason‐2 for understanding the geomagnetic storm (Astafyeva et al, 2015; Chen et al, 2016; Jin et al, 2017; Kuai et al, 2016; Nava et al, 2016; Prikryl et al, 2016). Meanwhile, the GPS scintillation events, LOL, and its effects on positioning service during the main phase were also demonstrated (Jacobsen & Andalsvik, 2016; Jin & Oksavik, 2018; Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…It also should be mentioned that the performance of our proposed strategy can also be affected by the number of data gaps caused by losses of signal lock since we did not consider the method to connect the data gaps yet. Several studies have been reported that, under extreme space weather event like the geomagnetic storm, several satellites may encounter losses of signal lock [46][47][48]. In this case, Banville and Langley [49] proposed a three-step method to estimate the size of signal interruption (cycle-slip) based on LAMBDA method in real-time kinematic PPP.…”
Section: Discussionmentioning
confidence: 99%
“…Deep signal fades that appear during small-scale irregularities effect result in navigation outages [29]. Luo et al [30] studied several strong storms during solar cycle 24, including the 17 March 2015 St. Patrick storm. They reported that the precise point positioning (PPP) error was less than 0.32 m at mid-latitudes.…”
Section: Introductionmentioning
confidence: 99%